PERAN ESTETIKA DALAM DAKWAH BAGI GENERASI MILENIAL - Ika Selviana (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2019)
Da'wah is basically an invitation in accordance with the origin of the Arabic word. Every invitation addressed to the da'wah target of religious knowledge has its own challenges and obstacles for a preacher. therefore it is necessary to have a touch of aesthetics in propaganda aimed at millennial generation through social media because they are more busy with cyberspace such as YouTube or Facebook. The aesthetic form of da'wah is the taste of a mad'u in enjoying da'wah from a preacher. A preacher must pay attention to maaddah (material), thoriqoh (method), and wasilah (media) in delivering his da'wah to mad'u. The method of preaching with the beauty of intonation of sounds, music, interludes of songs or blessings, as well as simple drawings is very popular with the millennial generation because it is more interesting and easy to understand, even the millennial generation likes young, outgoing, and pleasing to the eye lecturers.